PROBLEMS WITH FREE NUTRITIOUS EATING PROGRAM MENUS WITH NUTRITIONAL STANDARDS IN THE PERSPECTIVE OF LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Zahrotun Nisha Mayliana; Hanin Alya'Labibah; Muhammad Yasir (Justisi: Jurnal Ilmu Hukum, 2026)
The Free Nutritious Meal Program (MBG) is a strategic policy of the government in order to improve the quality of human resources and reduce malnutrition and stunting rates, especially among students. However, in its implementation, this program faces various problems, especially related to the fulfillment of nutrition standards and food safety. This study aims to analyze the problems of the Free Nutritious Eating Program menu from the perspective of Law Number 17 of 2023 concerning Health, with a case study of food poisoning that occurred at SMA Negeri 1 Kedungadem, Bojonegoro Regency. This research uses normative-empirical legal methods with legislative, conceptual, and case approaches. Data was obtained through interviews with the Bojonegoro Regency Health Office and the school, the distribution of questionnaires to students, and literature studies on relevant laws and regulations and legal literature. The results of the study show that the implementation of the MBG Program at SMA Negeri 1 Kedungadem has not fully met nutrition and food safety standards as stipulated in Law Number 17 of 2023 concerning Health. Cases of poisoning caused by Escherichia coli bacteria indicate weak supervision of the Nutrition Fulfillment Service Unit (SPPG), especially related to Laik Higiene dan Sanitasi certification and the application of the Hazard Analysis and Critical Control Point (HACCP) principle. This study concludes that although local governments have carried out their obligations in medical guidance, supervision, and handling, strengthening regulations and supervision by the National Nutrition Agency is still needed to ensure food safety and quality of the MBG Program in a sustainable manner.